Prophylactic efficacy of a novel method against postendoscopic papillary balloon dilation pancreatitis. Issue 5 (May 2019) - Natsui, Masaaki; Aoki, Yohei; Oka, Hiromitsu; Tsuboi, Kiyotaka; Tsubata, Shunsuke; Yoko, Kazumi; Sato, Toshifumi
Abstract : Objective: This study aimed to investigate whether a novel method including prophylactic pancreatic stent (PS) placement prevents postendoscopic papillary balloon dilation pancreatitis. Patients and methods: This study enrolled 200 consecutive patients with bile duct stones measuring up to 8 mm in diameter and retrospectively recruited 113 patients undergoing ordinary endoscopic papillary balloon dilation (EPBD) without PS placement from our previous study. In the novel method, EPBD and PS placement was attempted with a guidewire left in the main pancreatic duct for patients in whom stable guidewire placement in the main pancreatic duct was possible. EST was performed for patients in whom stable guidewire placement was impossible. The incidence rate of pancreatitis was compared between the novel method and ordinary EPBD, and risk factors for pancreatitis were analyzed. Results: Of 194 patients undergoing the novel method, EPBD and EST were performed in 180 and 14 patients, respectively. Following EPBD, PS placement was successful in 177/180 (98.3%) of patients. Pancreatitis occurred in 7/194 (3.6%) of patients after the novel method and 9/113 (8.0%) of patients after ordinary EPBD. There was a trend toward lower incidence rate of pancreatitis in the novel method. Stent dislodgement by the first postoperative morning and no previous endoscopic nasobiliary drainage (ENBD) were identified as risk factors for pancreatitis after EPBD with PS placement. No previous ENBD was also identified as a risk factor for pancreatitis after ordinary EPBD. Conclusion: Our novel method is likely to be superior to ordinary EPBD in preventing pancreatitis. Previous ENBD may prevent post-EPBD pancreatitis regardless of PS placement.